Perencanaan Strategis Madrasah dalam Menghadapi Tantangan di Era Digital - Siswahyuningsih, Zahrotunnisa`; Jaswadi, Jaswadi; Sulistyorini, Sulistyorini; Chotimah, Chusnul (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
This study examines the strategic planning of madrasas and the challenges faced by madrasas in the digital era. Strategic planning is a way for madrasas to face challenges in the digital era well. The research approach used is qualitative with a case study research method. Data was obtained in the form of interviews, observations, and documentation of the Flagship MI of AL Azhaar. The results of this study show that MI Unggulan Al Azhaar as an Islamic educational institution faces various problems and challenges in the digital era. MI Unggulan Al Azhaar continues to make breakthroughs to be able to adapt and improve its existence in the digital era. The author concludes that strategic planning is the basis for madrasas in carrying out challenges in the digital era, but it also needs to be followed by digitally capable human resources.Keywords: Strategic Planning, Challenges, Madrasah, Digital Era